Analysis of Factors Related to 3R-Based Waste Management Site in Jambi City - Jalius; Wahyu Ningsih; Syafril Hadi (Jurnal Pembangunan Berkelanjutan, 2020)
The objective of this study is to analysis of factors related to the functioning of 3R-based waste management site in Jambi City. The factors are consists of internal factors and external factors. The internal factors are individual characteristic (age, gender, job status, education, income), knowledge and attitude. The external factors are regulation, community participation and local government support. Design of this study is cross sectional design with 100 respondents as the samples. Proportional stratified random sampling is used as sampling technique and questionnaire is used to collect the data. The result of this study showed that the good functioning of 3R-based waste management site is 56%, and 44% has bad functioning. Based on Chi Square test showed that there were factors related to the functioning of 3R-based waste management site. They were knowledge, attitude, community participation and local government support. Based on linier regression test showed that community participation (95% CI: 0,815-9,661) was the most dominant factor related to the functioning of 3R-based waste management site which are controlled by knowledge, attitude and local government support. The conclusion of this study is to increase the functioning of 3R-based waste management site in Jambi City, the community participation have to developed by increasing the education about waste management with 3R-concept, also the increasing of local goverment support by coaching about the importance of 3R-based waste management site in Jambi City.